Terrorism: the never-changing chameleon - Filippidou, Anastasia (Taylor & Francis, 2023)
The chapter examines the duality of terrorism, by focusing on the constancy of its foundations, and by also analysing the continually changing surface of terrorism. The former refers to the causes and fundamentals of terrorism, and the latter concentrates on its means and tactics, which is its chameleonic nature. The chapter demonstrates that although terrorism constantly changes, it simultaneously remains the same. A range of factors is behind current and future terrorism, and the chapter summarises these into 5Ds, that is development, deprivation, decision-making, depletion and demographics. Moreover, the intensity and effects of these 5Ds are going to be experienced unevenly across different regions and countries further accelerating causes for conflict and straining counterterrorism efforts. Within this context, even though terrorism has ancient roots, it becomes an emergent problem meaning the way in which complex systems and patterns arise out of a multiplicity of interactions. Consequently, future terrorist trends and means will include creative repetition, while states will need to avoid responses of non-creative repetition and instead focus on intentional adaptation. Through a variety of examples, the chapter illustrates the complexity of terrorism and develops a predictive model for future trends of terrorism and violent extremism.